Perspectives on Learning: Methodologies for Exploring Learning Processes and Outcomes - Susan R Goldman (EARLI, 2014)
The papers in this Special Issue were initially prepared for an EARLI 2013 Symposium that was designed to examine methodologies in use by researchers from two sister communities, Learning and Instruction and Learning Sciences. The four papers reflect a common ground in advances in conceptions of learning since the early days of the "cognitive revolution" in the 1960s. This commentary shows the interdependence between advances in theory and advances in methodologies. Four shifts in conceptions of learning are described. That these shifts are evident in the work of both communities suggests a blurring of the boundaries between the two.